MAPPING THE NINETY YEARS OF ACTIVISM : Women’s movements in Mongolia - Ts.Tsetsegjargal (Acta Mongolica, 2011)
Women’s movements in various forms have existed thought history, and they have progressed in various diverse manners, supported in terms of both time and location. A Women’s movement have mainly focused on women’s equal opportunities in every preference in education, in various important social affairs, and as demanded in other reformist movements, but primarily insist that equal opportunities can be protected by abolishing gender inequality. From the early twentieth century until the present, Asian feminists were experts at reading the situation ‘on the ground’ and were not only selective about what aspects of feminist thinking globally they could adopt their directions from, but were also passionate about demonstrating their critiques to international platforms. The process of indigenizing feminisms and modifying international feminisms often occurred in a transnational ‘mental space’ with organizing and lobbying for legislative change often invoked the help of allies overseas or appeals to international bodies. Although activists in Asia were global actors, and although they were clearly influenced by Western feminisms, some women’s movements in Asia are more a product of the national than global influences. After a century of women’s activism in Asia it is timely for both scholars and activists to look back and reflect on the history of women’s movements in the region. Each Asian country’s women’s movement experienced its own struggles with the issue of class. Also, not all Asian countries could boast the ownership of a clearly organized movement for female enfranchisement. But this did not mean that there were no women’s movements there in the 1920s and 1930s. Like their sisters in the Western societies, the fight for the vote was also closely tied to the very notion of the ‘modern woman’ or the ‘new woman’.